Characterisation of bitumen, refined waste oil, and emulsifiers for coating and insulation purposes - Obi, Nasreldeen Ishag; Mohd Najib, Razali; Abdurahman, Hamid Nour (IOP Publishing, 2021)
The current study aims to characterise bitumen, refined waste oil, and emulsifiers to formulate emulsified modified bitumen for coating and insulation purposes. These raw materials were characterised in terms of their physical properties and elemental composition. This analysis provides significant information for setting the formulation parameters and determining the coating application conditions. Bitumen is a non-renewable petroleum substance; thus, the utilisation of refined waste oil in bitumen modification will reduce the dependency on neat bitumen and solve the increasing environmental problems in Malaysia. The physical characterisation was carried out using the tests of viscosity, flash point, density, penetration, softening point, moisture content, and X-ray diffraction. Fourier transform infrared analysis was conducted to determine the molecular composition and structure of the materials. In conclusion, the characterised materials showed the potential properties to formulate a highly adhesive, stable, and homogeneous emulsion.